2007
DOI: 10.1039/b610888a
|View full text |Cite
|
Sign up to set email alerts
|

Integrated continuous microfluidic liquid–liquid extraction

Abstract: We describe continuous flow liquid-liquid phase separation in microfluidic devices based on capillary forces and selective wetting surfaces. Effective liquid-liquid phase separation is achieved by using a thin porous fluoropolymer membrane that selectively wets non-aqueous solvents, has average pore sizes in the 0.1-1 microm range, and has a high pore density for high separation throughput. Pressure drops throughout the microfluidic network are modelled and operating regimes for the membrane phase separator ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
324
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(328 citation statements)
references
References 21 publications
0
324
0
4
Order By: Relevance
“…1b, inset. Capillary force-based separation. Very few reports on membrane separation 25,32,33 and microfluidics 34,35 have used the difference in capillary forces acting on the two phases as the primary mechanism to separate emulsions or dispersions. We call this methodology capillary force-based separation (CFS).…”
Section: Wetting Behaviour Of Water and Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…1b, inset. Capillary force-based separation. Very few reports on membrane separation 25,32,33 and microfluidics 34,35 have used the difference in capillary forces acting on the two phases as the primary mechanism to separate emulsions or dispersions. We call this methodology capillary force-based separation (CFS).…”
Section: Wetting Behaviour Of Water and Oilmentioning
confidence: 99%
“…This is significantly lower than the flux of the water (µ~1 mPa s), Q water = 509,000 l m − 2 h − 1 , predicted using the Hagen-Poiseuille relation 37 . This is because the number of pores through which water is flowing at any given time (so-called 'active pores') in CFS can be significantly lower (~1 − 10%) than the actual number of pores 35 .…”
Section: Separation Of Free Oil and Watermentioning
confidence: 99%
“…Segmented flow can eliminate Taylor dispersion by localizing samples as aqueous droplets or plugs formed in a stream of water-immiscible carrier fluid. [22][23][24][25] A surge of recent research into segmented flows has shown the potential of this approach for chemical measurement. Droplets or plugs from femtoliter to microliter volume can be reproducibly created using a variety of microfluidic geometries including tee junctions, 26 Yjunctions, 23 The goal of this study was to combine in vivo microdialysis sampling with a segmented flow microfluidic device to conserve temporal resolution while sample plugs were transported from the probe to a downstream detection system.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 While in analytical chemistry this application has become a standard approach for sample enrichment and isolation, 1−3 this function did not find its integration in the chemical engineering toolbox until recent years, with the emergence of microreaction technology. 4,5 The aim of this relatively new field is the enhancement of phenomena such as mass transfer and heat transmission via large area to volume ratios, while taking advantage of surface tension effects at a small scale. 5,6 These principles should be conserved across different scales of operation using a scaling-out approach, i.e.…”
Section: Introductionmentioning
confidence: 99%